SYSTEMATIC LITERATURE: TANTANGAN DAN INOVASI MANAJEMEN DALAM MENGELOLA PASAR MONOPOLI DI ERA GLOBAL - Arafah, Zahid Nugrah; AZ, Bambang; Al Faisal, Aldi; Zefriyenni, Zefriyenni (Jurnal Daya Saing, 2025)
This study presents a Systematic Literature Review (SLR) on challenges and innovations in managing monopoly markets in the global era. The research collected articles published between 2015 and 2025 from Scopus, Web of Science, Dimensions, and Google Scholar following PRISMA guidelines. Through a rigorous selection process, eleven relevant articles were selected for further analysis. The findings reveal that monopoly markets in the digital era face complex challenges in the form of tension between innovation needs and antitrust regulations, where overly strict antitrust policies potentially hinder innovation incentives for dominant companies. The development of digital platform economies further complicates this dynamic through the formation of "data monopolies" that consolidate market power through algorithm and information control. Bibliometric analysis using VOSviewer identified four main research clusters: regulatory model development, managerial approaches, digital market dynamics, and sectoral applications. This study asserts that effective monopoly market management requires an adaptive regulatory approach that not only focuses on restricting monopoly power but also encourages collaboration between government, business actors, and academics in designing evidence-based policies. The research provides theoretical and practical contributions to developing market management policies capable of maintaining balance between economic growth, consumer protection, and promotion of healthy competition in an increasingly complex digital era. Keywords: managerial economics, innovation, challenges, monopoly